Increasing the level of reuse of complete process models in a process modelling repository - Veitch, Ross Shearer (Department of Information Systems, 2026)
Business Process Modeling has become a common activity in organisations. However, as the number of process models increases, so too does the number of duplicated models increase, and the level of process model reuse has been found to be surprisingly low. In organisations which operate in an environment with multiple channels, products and customer types, complete process model reuse becomes especially challenging. While the value of process modeling increases with process model reuse, this study also considered the system dynamics arising from not reusing process models. Therefore, the motivation for this study was to increase the level of reuse of process models in a repository. To answer the research questions, a pragmatic research paradigm was adopted. Using a DSR strategy, a new modeling method was designed and tested in a real-world setting in a large South African financial services organisation. A mixed-methods approach was used, consisting of semi-structured interviews conducted with modellers, and a quantitative analysis of the process repository. The new modeling method incorporates reuse concepts from the software development domain. This study makes three contributions to knowledge. Firstly, it describes the consequences for the organisation, using system dynamics, of not reusing process models, and illustrates how vicious cycles are established which result in continually increasing costs. Secondly, the study develops a measure which can be used to determine the level of process model reuse in a process repository. Finally, this study develops a new modeling method which increases the level of reuse of process models in a process repository. This research project was carried out in a single organisation. Data collection from semi- structured interviews was limited to those process modellers who were using the new modelling method. It is possible that other modellers could identify additional factors impacting the consequences of not reusing complete process models. The new modeling method designed is dependent on the underlying architecture of the modeling tool in use. Therefore, this method will not be suitable for every available process modelling tool. This research project also offers the vendors of process modeling tools opportunities to further enhance their products by incorporating elements of the new method to facilitate the increased reuse of complete process models by users.